If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + y = 0 Reorder the terms: -2 + 3x + y = 0 Solving -2 + 3x + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 3x + 2 + y = 0 + 2 Reorder the terms: -2 + 2 + 3x + y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3x + y = 0 + 2 3x + y = 0 + 2 Combine like terms: 0 + 2 = 2 3x + y = 2 Add '-1y' to each side of the equation. 3x + y + -1y = 2 + -1y Combine like terms: y + -1y = 0 3x + 0 = 2 + -1y 3x = 2 + -1y Divide each side by '3'. x = 0.6666666667 + -0.3333333333y Simplifying x = 0.6666666667 + -0.3333333333y
| =217s-7 | | 2x+5x^2=30 | | a+-4a+-3a= | | -x+4=-y | | 2x+15x^2=24 | | 7.6-0.7h+1.2-1.3h=24-2.0h-6.7 | | 6.9x-3.6=24.0 | | 6y^2=-7-2 | | 8/3x-21/2 | | 2x+15x^2=32 | | 5x5/5/7 | | 128=8-4e | | 45x+27= | | 2x+15x^2=35 | | x^3+5x^2-4x-2=0 | | 25=-5y-6x | | -6w^2+150w=0 | | 5(2x-17)=10x-85 | | 5x+x^2=y | | -13+3x+4+-5x=15 | | 0.06x-0.10(x-2)=0.02(8) | | 36+7-25+7= | | 4x-15/3=7 | | -2(7x-4)+3(5x-4)-3=7-3 | | 28+p=39 | | 10g+10=29g | | 17.40=1.5n | | 3y=8-2x | | 3x+4(x-8)= | | -7r+14=-71 | | -4(3x+6y)+12x+4y= | | 12x+.50y=112 |